Consequences of the Use of Political Money Crimes in Indonesian Election Administration - Khomaidi Hambali Siambaton; Mohd. Din; Faisal Akbar; Mahmud Mulyadi (Green Publisher, 2025)
Democracy is a fundamental principle in most modern states, and elections serve as a key expression of people’s sovereignty. However, in Indonesia, political money crimes, such as money politics, threaten the integrity of the democratic process. The aim of the research is to explore the legal challenges and loopholes in the election system that facilitate the rise of such criminal activities. The research employs an empirical and normative-juridical approach, utilizing case data from general elections and various legal analyses. The findings reveal significant weaknesses in the electoral framework, particularly regarding the enforcement of regulations during the campaign and voting periods, leading to widespread vote-buying. Furthermore, the research highlights that the legal provisions governing electoral offenses are insufficient to deter money politics, as they fail to encompass all potential perpetrators, particularly those outside campaign teams. The implications of this research suggest a need for stricter legal measures and improved oversight mechanisms to ensure the legitimacy of elections and uphold democratic principles.